Solution to avoid mistakes done by the contractor in tender submission / Megat Aridh Ilmi and Mohd Esham Mamat - Ilmi, Megat Aridh; Mamat, Mohd Esham (2020)
The contractor's common mistakes in tender submission for government project is inevitable. Therefore, this research is conducted to analyse the common mistakes done by contractors in their tender submission, the effect of mistake done by contractors in PWD Tender submission process and to suggest the solution to avoid the mistake done by the contractor. In order to achieve the objectives of the research, the data and information are collected using primary and secondary data. The secondary data are written and published sources collected through books, articles, newspaper, websites and journals. The objectives of this research are (i) to identify the common mistake done by the contractor in tender submission, (ii) the effect of mistakes done by the contractor in tender submission and lastly, the solution to avoid mistakes done by the contractor in tender submission. This research has potential benefit to the employers or individuals who are involved in construction because it can help them to identify the mistakes done by the contractor and know how to deal with the problem after that.